Analisis Konsep Pemikiran Dr. Zakiah Daradjat tentang Ma’rifatul Insan dan Relevansinya terhadap Potensi Manusia sebagai Makhluk - Masyhuri Masyhuri; Muhammad Fatcul Huda (Ikhtisar: Jurnal Pengetahuan Islam, 2022)
Humans are beings whose minds are completely given by Allah. With their minds, humans are able to think so that they can achieve new knowledge to be processed and developed into science. To achieve and gain knowledge, humans must go through educational process, if the potency is not enhanced otherwise it will be less meaningful in life. Thus, it needs to be developed and the development will always be obtained through efforts and educational process. This qualitative paper aims to investigate the nature of humans as beings as well as how humans develop their potencies. It also attempts to depict Ma’rifatul Insan and Humans’ potencies as beings based on Zakiah Daradjat’s concept. The data sources of the library research were elicited and analyzed to be investigated critically and systematically. The results show that the nature of humans as beings is noble. Additionally, Allah bestowed mind that able to differentiate either good or bad if compared with other beings. The human’s development is carried out through efforts and educational process that brings the development of potency for religious instincts. Based on Zakiah Daradjat’s concept, humans’ roles as beings are prayer to Allah, being a caliph on earth and as the servants of Allah, it should be commit toward Islam as a religion.